Chapter Tres ingenios al servicio de un canónigo: de La cortesana en la sierra... a L'infanta villana de Carlo Celano - MARCELLO, Elena Elisabetta (Studi e saggi, 2020)
Analysis of the seventeenth-century theatrical adaptation of the Neapolitan Carlo Celano, L'infanta villana, and the Spanish source identified, La cortesana en la sierra y fortunas de don Manrique de Lara, written in collaboration by Juan de Matos Fragoso (I act), Juan Bautista Diamante (II act) and Juan Vélez de Guevara (III act). It focuses in particular on two sequences - one serious and one comic - that allow to verify the degree of dramatic and rhetorical adaptation and the translatability of humor compared with the prototext.